Global and pedestal confinement and pedestal structure in dimensionless collisionality scans of low-triangularity H-mode plasmas in JET-ILW. (11th October 2016) - Frassinetti, L.; Beurskens, M.N.A.; Saarelma, S.; Boom, J.E.; Delabie, E.; Flanagan, J.; Kempenaars, M.; Giroud, C.; Lomas, P.; Meneses, L.; Maggi, C.S.; Menmuir, S.; et al.
Abstract: A dimensionless collisionality scan in low-triangularity plasmas in the Joint European Torus with the ITER-like wall (JET-ILW) has been performed. The increase of the normalized energy confinement (defined as the ratio between thermal energy confinement and Bohm confinement time) with decreasing collisionality is observed. Moreover, at low collisionality, a confinement factor H98, comparable to JET-C, is achieved. At high collisionality, the low normalized confinement is related to a degraded pedestal stability and a reduction in the density-profile peaking. The increase of normalized energy confinement is due to both an increase in the pedestal and in the core regions. The improvement in the pedestal is related to the increase of the stability. The improvement in the core is driven by (i) the core temperature increase via the temperature-profile stiffness and by (ii) the density-peaking increase driven by the low collisionality. Pedestal stability analysis performed with the ELITE (edge-localized instabilities in tokamak equilibria) code has a reasonable qualitative agreement with the experimental results. An improvement of the pedestal stability with decreasing collisionality is observed. The improvement is ascribed to the reduction of the pedestal width, the increase of the bootstrap current and the reduction of the relative shift between the positions of the pedestal density and pedestal temperature. The EPED1 model predictions for the pedestal pressure height are qualitatively well correlated with the experimental results. Quantitatively, EPED1 overestimates the experimental pressure by 15–35%. In terms of the pedestal width, a correct agreement (within 10–15%) between the EPED1 and the experimental width is found at low collisionality. The experimental pedestal width increases with collisionality. Nonetheless, an extrapolation to low-collisionality values suggests that the width predictions from the KBM constraint are reasonable for ITER.